The use of well amongst native speakers of English observed on the basis of CHILDES database. The comparison of Wells and Fletcher corpora (Conversatoria Linguistica, 2019)
Discourse markers are part and parcel of linguistic behavior of speakers of all languages. In more reserved societies, people tend to express greater distance to other people. In more open societies, speakers maintain closer proximity with others, and are more inclined to preserve greater intimacy with people they come into contact with. All the same, depending on the society using the language, different forms of complementation of literal semantic meanings are used. In some cultures speakers feel, that apart from words, they need to respond to what other people say with, be it a gesture, a facial expression or an interjection. This reaction might be received as a kind of mockery by speakers of other languages. Native speakers of English seem to be more concerned with the point of view of their interlocutors. Whereas in some languages simple no! is enough to express disagreement, in English, a more likely response includes a discourse marker such as well, for instance. This well opens a plethora of interpretations, disagreement among them, but at the same time does not deprive the interlocutor of some degree of rightness. This paper discusses the problem of the use of well amongst native speakers of English, observed on the basis of CHILDES database.